2021
DOI: 10.7150/ijbs.53126
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in a sarcopenia model of senescence accelerated mouse prone 8 (SAMP8)

Abstract: As a systemic syndrome characterized by age-associated degenerative skeletal muscle atrophy, sarcopenia leads to a risk of adverse outcomes in the elderly. Age-related iron accumulation is found in the muscles of sarcopenia animal models and patients, but the role of iron in sarcopenia remains poorly understood. It has been recently found that iron overload in several diseases is involved in ferroptosis, an iron- dependent form of programmed cell death. However, whether this excess iron can result in ferroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 41 publications
(58 reference statements)
2
37
2
Order By: Relevance
“…The aim of the present study was to investigate whether iron overload reflecting pathophysiological conditions impacts skeletal muscle structure, cellular mechanisms regulating iron metabolism, or muscle atrophy. In response to iron overload close to clinically relevant levels, our data contrast with previous studies, 23 , 24 , 32 , 33 as excess iron did not induce muscle atrophy. Indeed, FAC‐treated myotubes and iron dextran supplementation in mice induced iron accumulation in cells and skeletal muscle, but neither muscle atrophy nor activation of key signalling pathways involved in proteolysis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The aim of the present study was to investigate whether iron overload reflecting pathophysiological conditions impacts skeletal muscle structure, cellular mechanisms regulating iron metabolism, or muscle atrophy. In response to iron overload close to clinically relevant levels, our data contrast with previous studies, 23 , 24 , 32 , 33 as excess iron did not induce muscle atrophy. Indeed, FAC‐treated myotubes and iron dextran supplementation in mice induced iron accumulation in cells and skeletal muscle, but neither muscle atrophy nor activation of key signalling pathways involved in proteolysis.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with these findings and our in vitro results, no reduction in muscle weight and fibre size compared with control animals was observed in iron‐treated mice. Such data contrast with previous studies reporting that iron overload promotes skeletal muscle atrophy in mice 23,24,32 . However, experimental protocols used in those studies induced a systemic and muscle iron overload largely beyond the classical findings observed in pathophysiological conditions.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our observations, studies in neuronal and retina epithelial cells have revealed that ferroptotic compounds are able to promote cellular senescence [96][97][98]. Whether cellular senescence promotes sensitization [97,99] or resistance [100] to ferroptosis is currently still under debate. The ferroptosis-driven epigenetic changes characterized in this study seem to suggest that RSL3-mediated oxidative stress orchestrates DNA damage and genomic instability, which induces premature cell senescence and prompts activation of DNA repair genes such as NR4A2.…”
Section: Discussionsupporting
confidence: 91%
“…There is growing evidence that elevated reactive oxygen species (ROS) and increased local oxidative stress caused by excess iron may play an important role. In one hand, ROS can cause lipids, proteins, mitochondria, and nucleic acids damage, finally resulting in cellular dysfunction and ferroptosis ( 14 , 24 , 31 ). On the other hand, oxidative stress may lead to muscle tissue damage by increasing expression of inflammatory cytokines, such as interleukin-1 (IL-1), tumor necrosis factor-α (TNF-α), and IL-6 ( 32 ).…”
Section: Discussionmentioning
confidence: 99%